Effective Teaching Program on Knowledge and Attitude about Disaster Management: An Overview - Thakur, Nitika; Solomon, Smriti G. (International Journal of Nursing and Medical Investigation, 2024)
Disaster management is a comprehensive approach to both preventing and responding to disasters. All aspects of preparedness, rescue, relief, and rehabilitation activities, as well as preventive and protective measures, are included in disaster management. India’s natural landscape is incredibly diversified, and as a result, a significant share of the reported catastrophe victims in Asia in 2015 was from India. Due to its unique geo-climatic conditions, the country is among the ones that are most susceptible to natural disasters in the world. Disaster nursing is the adaptation of professional nursing knowledge, skills, and attitude in recognizing and meeting the nursing, health, and emotional needs of disaster victims. Nurses occupy a unique role in lobbying for organized, profit-driven healthcare amid emergencies. Nurses are necessary to prevent, monitor, and react to any circumstance. Due to the small sample size of the study, the nursing students’ understanding of and attitudes regarding disaster management and emergency preparedness were lacking. Nursing students may benefit from a disaster nursing education program that will increase their preparedness for and awareness of disasters. It was discovered that the disaster nursing and management teaching program offered to nursing students improved attitudes toward overall preparedness for disasters, self-efficacy in disaster response, and psychological resilience. Disaster management teaching has a significant impact on nursing students’ degree of preparedness for emergencies and knowledge.